Methodological design and validation of a virtual proposal for the creation of a school of leadership and development of creative thinking in higher education - Barrera Caro, Zoe Leyda Carolina; Cárdenas Sierra, María Érica Marcela (Rastros Rostros, 2022)
Higher education poses new challenges and highlights the need to rethink the pedagogical strategies implemented, where today’s students seek motivating and relevant learning in different challenging environments that allow them to create, argue, debate and generate ideas that connect to their reality. This article shows the findings of the pilot test of the virtual course: leadership school, for the development of creative thinking competencies carried out with undergraduate students of the Bucaramanga campus of the Universidad Cooperativa de Colombia. The method is based on action research with a qualitative approach under an inductive logic as a reasoning process that goes from the particular to the general, through the perceptions of students as a baseline for the identification of needs and opportunities for improvement of the school. The results allow concluding how leadership can be promoted in a multidisciplinary way and game-based learning as an active methodology for the development of creative thinking articulated to the curricula of higher education; from a view that visualizes the student in an integral way and respects his singularity, besides offering the opportunity for change in the conceptions of competencies required so that every individual, not only can develop them in a specific discipline. For future studies, it is important to consider the methodological strategy and the time available for the implementation of leadership projects that have an impact on the personal and professional aspects of the participants.
Keywords: leadership; creativity; strategies; learning; competencies; methodologies